2015
DOI: 10.1159/000381702
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Coronary Artery Stenoses, Markis Class, and Ectasia Ratio in Patients with Coronary Artery Ectasia

Abstract: Objectives: To assess the prognostic value of coexisting coronary artery disease (CAD), Markis class, and ectasia ratio for major adverse cardiovascular events in patients with coronary artery ectasia (CAE). Methods: A total of512consecutive patients with angiographically proven CAE were enrolled. Coronary ectasia extent was graded using the Markis class, and ectasia severity was assessed based on the ectasia ratio. Patients were followed up for a median of 34.6 months. Results: In the current study, 76 cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 22 publications
1
18
1
7
Order By: Relevance
“…Similar to prior studies, we found that the RCA was most commonly affected by ectasia followed by the LAD and the circumflex (Table ). We found an almost equal distribution of the four Markis types in our cohort.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Similar to prior studies, we found that the RCA was most commonly affected by ectasia followed by the LAD and the circumflex (Table ). We found an almost equal distribution of the four Markis types in our cohort.…”
Section: Discussionsupporting
confidence: 89%
“…We had a nearly equal distribution of isolated CAE (46%) and CAE with CAD (54%). Most prior studies have reported a much lower prevalence of isolated CAE and this is also likely related to geographic variations or study inclusion criterion (in case of CASS registry). Most studies have not reported on the prevalence of sluggish flow.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Логично предположить, что, как и у больных с фибрилляцией предсердий, усиление антитромботической терапии за счет добавления второго антиагреганта не приведет к существенному снижению риска тромбозов АКА. Полагают [4,22,23], что препаратами выбора при данной патологии могут быть антикоагулянты, опыт использования которых, к сожалению, ограничивается относительно небольшими наблюдательными исследованиями и регистрами. Одно из наиболее показательных исследований [17] включало 1698 больных с инфарктом миокарда, подвергнутых ангиографии с последующим инвазивным лечением.…”
unclassified